Spontaneous Adverse Drug Reaction Monitoring in a Tertiary Care Centre - Kaur, Kirandeep; Kanwal, Preet; Goyal, Pardeep; Singh, Paramjit; Yakhmi, Sahil; Jain, Samriti; Kaushal, Sandeep (Current Drug Safety, 2020)
Background and Objective: Adverse drug reactions (ADRs) are associated with increased economic burden on the society. Monitoring of ADRs can help in decreasing the incidence of preventable adverse reactions. Methods: Under Pharmacovigilance Program of India, collection and reporting of ADRs has been going on at Dayanand Medical College and Hospital since January 2011. Here, we have analyzed the individual case safety reports (ICSRs) reported and uploaded between January 2017 and June 2019 from our centre. The ADR form provided by PvPI was used for collecting information, and the causality assessment was done according to the WHO-UMC scale. Results: A total of 498 ICSRs were uploaded through Vigiflow software during this period. Highest number of ADRs were recorded in the age group of 31-45 years (29.01%) and the least number of ADRs were recorded in the children less than 15 years of age (6.76%). General Medicine ward reported the highest number of ADRs and the antibiotics were most commonly associated with ADRs (26.21%), followed by antipsychotics (13.83%) and NSAIDs (12.14%). More than 90% of ADRs were non-serious (93.17%) and most of the ADRs were skin and soft tissue related (49.20%). Conclusion: Spontaneous reporting among indoor patients shows highest number of ADRs with use of antibiotics and almost all of the ADRs were non-serious in nature. Almost half of the total ADRs were skin and subcutaneous tissue related. Continuous efforts are required for further strengthening of the pharmacovigilance program of India.
Keywords: pharmacovigilance